PENGARUH MEDIA PAPAN KANTUNG PINTAR TERHADAP KECERDASAN KOGNITIF ANAK USIA 5-6 TAHUN DI PAUD LESTARI CIKERAI - Yulita, Dewi (Program Studi Pendidikan Islam Anak Usia Dini - IAI Muhammadiyah Bima, 2025)
The influence of smart pocket board media in improving children's cognitive abilities in group B aged 5-6 years at PAUD Cikerai. Dewi Yulita.Children's cognitive abilities have not developed well, as seen by many children who have difficulty saying numbers 1-10 properly and correctly. This is due to the lack of stimulation provided and the media used in learning is still less interesting for children. The purpose of this study was to determine how much influence the smart pocket board media has in improving children's cognitive abilities in group B aged 5-6 years at PAUD Cikerai. The research method used a quantitative approach with a pre-experimental method with a sample of 16 children. The data analysis technique used a one group pretest-posttest design, namely knowing children's cognitive abilities before using the smart pocket board media as variable X1 and after using the smart pocket board media as variable X2, the data were analyzed using SPSS version 24. The results of the study showed that children's cognitive abilities before using the smart pocket board media were still not developed. the value obtained by children was 29.54%, while after using the smart pocket board media the value obtained by children was 81.53%. The difference in cognitive abilities before and after using the smart pocket board media was carried out using a two-sample t-test, obtaining t count (30.48) > t table (2.131), which was then tested using the hypothesis with the provision that if t count ≥ t table then Ho is rejected, which means there is a significant difference in the cognitive abilities of group B children at PAUD Cikerai between before and after using the smart pocket board media.